Preliminary investigation of Culicidae species in South Pantanal, Brazil and their potential importance in arbovirus transmission Investigação preliminar das espécies de culicídeos do Pantanal Sul brasileiro e sua potencial importância na transmissão de arbovírus - Alex Pauvolid-Corrêa; Fernando Neto Tavares; Jeronimo Alencar; Julia dos Santos Silva; Michele Murta; Nicolau Maués Serra-Freire; Aiesca Oliveira Pellegrin; Hélcio Gil-Santana; Anthony Érico Guimarães; Edson Elias da Silva (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
In view of the high circulation of migratory birds and the environmental and climatic conditions which favor the proliferation of arthropods, the Brazilian Pantanal is susceptible to circulation of arboviruses. However, the amount of data concerning arbovirus vectors in this area is scarce; therefore the aim of this study was to conduct a preliminary investigation of Culicidae species in the Nhecolândia Sub-region of South Pantanal, Brazil and their potential importance in the arbovirus transmission. A total of 3684 specimens of mosquitoes were captured, 1689 of which caught in the rainy season of 2007, were divided into 78 pools and submitted to viral isolation, Semi-Nested RT-PCR and Nested RT-PCR, with a view to identifying the most important arboviruses in Brazil. Simultaneously, 70 specimens of ticks found blood-feeding on horses were also submitted to the same virological assays. No virus was isolated and viral nucleic-acid detection by RT-PCR was also negative. Nevertheless, a total of 22 Culicidae species were identified, ten of which had previously been reported as vectors of important arboviruses. The diversity of species found blood-feeding on human and horse hosts together with the arboviruses circulation previously reported suggest that the Nhecolândia Sub-region of South Pantanal is an important area for arbovirus surveillance in Brazil. Regiões como o Pantanal brasileiro, que apresentam fatores como riqueza de fauna silvestre incluindo circulação de aves migratórias e condições ambientais e climáticas favoráveis à proliferação de artrópodes estão potencialmente sujeitas à circulação de arbovírus. Entretanto, poucos trabalhos foram realizados acerca da presença de arbovírus em potenciais vetores no Pantanal. Neste sentido o principal objetivo deste trabalho foi conduzir uma investigação preliminar para presença de arbovírus em amostragens de culicídeos capturados na Sub-região da Nhecolândia no Pantanal Sul. Um total de 3684 mosquitos foi capturado, dos quais 78 grupos compondo uma amostragem de 1789 espécimes foram submetidos às técnicas de isolamento viral e RT-PCR para os mais importantes arbovírus no Brasil. Simultaneamente, 70 espécimes de carrapatos capturados durante hematofagia em cavalos também foram submetidos à pesquisa viral. Não houve isolamento viral em nenhuma amostra analisada e os resultados de detecção de ácido nucléico viral foram também negativos. Entretanto, foram identificadas 22 espécies de culicídeos, dez das quais previamente reportadas como vetores de importantes arbovírus. A competência vetorial de espécies capturadas durante hematofagia em humanos e cavalos aliada ao relato prévio de circulação de arbovírus sugerem a Sub-região da Nhecolândia como uma importante área de vigilância para arbovírus no Centro-Oeste do Brasil.